Entrepreneurship Development in Higher Education Through Ve-Ice Carroli To Foster Student Entrepreneurial Interest - Idzaa Zubdatun Thoyyibah; Dian Candra Wati; Frizky Rahmadhani (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2019)
This article aims to foster student entrepreneurial interest in the millennial era. It is through Ve-Ice Carroli (Vegetables Ice Cream Carrot and Broccoli). The research method used is the study of literature. Data collection is done by studying books, literature, notes, and reports relating to the problem being solved. Literature sources in this study were obtained from books, journals, and research results. The results of this study include the process of identifying theories systematically, finding literature, and analyzing documents that contain information related to the research topic. The results of this study are in the form of the development of higher education entrepreneurship learning.